(untitled) (Research, Society and Development, 2020)
This study aims to evaluate the psychometric properties (validity and reliability) of the Hurt Insult Threatened Scream (HITS) instrument for the screening of domestic violence against the elderly. Participated in this sample 48 elderly people and descriptive and inferential statistics were used to analyze the results. Reliability was tested by measuring intra-observer agreement and internal consistency. Intra-observer agreement was verified in the HITS Brazil itens and in the total score by the Intraclass Correlation Coefficient (ICC), with the following classification: ICC <0.40, concordance. weak 0.41 <ICC <0.75, moderate agreement; and ICC> 0.75, high agreement. The internal consistency was evaluated by Cronbach’s alpha. The item-total correlation of the HITS Brazil was calculated, being the score superior to 0,4 considered satisfactory. It was verified that the average age of the elderly was 72± 6.3 years, being of the female sex (83%) of the white color (63%), the main agent of the violence was the spouse 30% followed by children (13%). It was found that most participants opted for the 80% color strategy to better scale the frequency of violence. The values obtained through Cronbach’s alpha coefficient for each item show satisfactory results (item 1: 0.80, item 2: 0,75, item 3: 0,80 and item 4:0,68). In its final version, HITS presented four items and maintained characteristics of the original version, in the analysis of internal consistency the instrument presented high results, showing to be a valid and reliable instrument for the use in the Brazilian culture.